The Effect of Using Mobile Branded Apps on the Purchase Intention in the Retail Industry among Saudi Females - Almeshal, Soad; Alshathri, Alhanouf (British Journal of Marketing Studies, 2019)
This paper aims to increase collective awareness of the importance of introducing E-commerce in businesses in Saudi Arabia. The easiest and the trendiest way is using branded mobile apps. The study investigates consumer purchase intentions using smartphone branded applications. More specifically, it studies whether a moderating variable such as brand loyalty and mediating variables such as trust and quality of the app affect the purchase intention. The usability of the app is the independent factor and the purchase intention is the dependent factor. The survey was conducted using an electronic and self-administered questionnaire. 167 questionnaires were answered. The response rate was 95%. The findings were that the usability of branded mobile apps highly affects the purchase intention among Saudi females in Saudi Arabia.